2023
DOI: 10.1002/bse.3450
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ESG news on the volatility of the Portuguese stock market—Does it change during recessions?

Cássio Zanatto,
Margarida Catalão‐Lopes,
Joaquim P. Pina
et al.

Abstract: This paper assesses how environmental, social, and governance (ESG) news influence Portuguese stock market volatility depending on the business cycle. Given the lack of an adequate index to capture the effects of ESG media on the Portuguese stock market, a News Sentiment Index is developed. This index, which captures positive and negative ESG news on companies listed in the Portuguese Stock Index (PSI‐20), is then used as an external regressor in symmetric and asymmetric GARCH‐type models employed to model the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
1
Order By: Relevance
“…However, the results of this study explain that corporate scandal has no influence on stock price volatility. This does not support signal theory and the efficient market hypothesis theory, and is not in line with research by Sandu (2023), Zanatto et al (2023), Cui & Docherty (2020), and Glasserman & Mamaysky (2019), which states that corporate scandal has an influence on increasing share price volatility.…”
Section: The Influence Of Corporate Scandal On Stock Volatilitycontrasting
confidence: 82%
See 1 more Smart Citation
“…However, the results of this study explain that corporate scandal has no influence on stock price volatility. This does not support signal theory and the efficient market hypothesis theory, and is not in line with research by Sandu (2023), Zanatto et al (2023), Cui & Docherty (2020), and Glasserman & Mamaysky (2019), which states that corporate scandal has an influence on increasing share price volatility.…”
Section: The Influence Of Corporate Scandal On Stock Volatilitycontrasting
confidence: 82%
“…This ultimately contributes to an increase in the volatility of a company's shares, which reflects the risk level of the shares in the market. This is evidenced by research by Sandu (2023) and Zanatto et al (2023) who found that ESG controversy and ESG news with negative sentiment had an influence on increasing stock volatility. However, further research is required, especially on the Indonesian stock market, which is still in its developing stage (emerging market) to deeply understand this phenomenon.…”
Section: Introduction *mentioning
confidence: 92%